Early resolution of troubled financial institutions: An examination of the accelerated resolution program - Stover, Roger D. (Journal of Banking & Finance, 1997)
This paper expands the empirical research on the auctions of failed financial institutions by examining the thrift industry Accelerated Resolution Program as an alternative to the standard auction procedures. Jointly managed by the Office of Thrift Supervision and the Resolution Trust Corporation, the objective of this program was to intervene before insolvency and, thereby, to reduce the regulatory expenditures. Previous research has often found the existence of a wealth transfer to the winning bidders in both commercial bank and thrift auctions. In contrast to this previous research, no evidence is found in this study to conclude that a wealth transfer occurred in standard Resolution Trust Corporation auctions. Furthermore, while the Accelerated Resolution Program yielded positive abnormal returns, there is also no evidence of a wealth transfer.